2015
DOI: 10.1039/c5md00131e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and anti-tubercular activity of conformationally-constrained and bisquinoline analogs of TMC207

Abstract: One of the most significant breakthroughs in the battle against tuberculosis is the recent approval of the quinoline compound, TMC207, for the treatment of drug-resistant tuberculosis. To gain insight into the molecular determinants of the activity of TMC207 and to evaluate the scope of quinoline compounds as antitubercular agents, we synthesized a series of TMC207 derivatives and evaluated their anti-tubercular activity. Making the lateral chain of the drug rigid by linking it to an adjacent phenyl substituen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…In the same year, Kalia et al reported the synthesis of conformationally constrained and bisquinoline analogs of TMC207 and investigated their antitubercular activity ( Kalia et al, 2015 ). Constricted analogs of TMC207 were prepared using benzyl quinoline anion with proper cyclic ketone analogs of the Mannich base as reported earlier ( Guillemont et al, 2011 ).…”
Section: Synthesis and Antitubercular Activity Of Heterocyclic Moietiesmentioning
confidence: 99%
“…In the same year, Kalia et al reported the synthesis of conformationally constrained and bisquinoline analogs of TMC207 and investigated their antitubercular activity ( Kalia et al, 2015 ). Constricted analogs of TMC207 were prepared using benzyl quinoline anion with proper cyclic ketone analogs of the Mannich base as reported earlier ( Guillemont et al, 2011 ).…”
Section: Synthesis and Antitubercular Activity Of Heterocyclic Moietiesmentioning
confidence: 99%
“…Conformationally constrained and bisquinoline (replacing a phenyl substituent of TMC207 with a quinoline moiety) analogues of TMC207/bedaquiline have been reported to gain insight into the molecular determinants of the activity of TMC207. However, drug rigidity of lateral chain resulted in a decrease in activity, but bisquinolines demonstrated potent antitubercular activity in in vitro experiments and also in in vivo mouse model of the disease (Kaliaa et al, 2015). Additionally, a novel series of aryl sulphonamide derivatives of amodiaquine (Khana et al, 2013;Singh et al, 2013) have been investigated for selective mycobacterial ATP synthase inhibitory activity against both replicating and non-replicating M. tuberculosis resulting in ATPase inhibitory activities (IC50) of these compounds that range between 0.36 and 5.45 µm (Singh, Roy, et al, 2015).…”
Section: Mtb Energy Metabolismmentioning
confidence: 99%
“…Pentacyclo‐undecane derivatized tetra‐amines having tertiary amine units in the cyclic form were prepared and found to be potent antitubercular agents . Bisquinoline analogs of TMC207 and conformational‐constrained molecules possessing tertiary amine unit were reported, and they possessed remarkable antitubercular potency . A set of 9‐benzylpurines possessing tertiary amine unit was synthesized among which 2‐chloro‐4(2‐furanyl)‐9‐benzylpurine was reported to inhibit Mycobacterium tuberculosis H 37 R V with lowest minimum inhibitory concentration (MIC) value .…”
Section: Introductionmentioning
confidence: 99%